2004
DOI: 10.1108/14777270410536358
|View full text |Cite
|
Sign up to set email alerts
|

Clinical governance: a fresh look at its definition

Abstract: Clinical governance was introduced in 1997 as a comprehensive framework to improve the healthcare quality in the National Health Service. Since then, the proliferation of various definitions and models of clinical governance illustrates that different perceptions are emerging on clinical governance. However, none of these definitions captures the essence of clinical governance in terms of its organisation-wide implications for continuous quality improvement. Although there is discrete mention of structure, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…In NHS study, 67% of responsible officers reported that they are ready to implement CG with consideration to "proactive risk management" dimension. This finding is in consistent with some of other studies (6,9,25,26). In these studies, preceding dimension has been considered as the most effective factor for quality improvement and facilitation of CG implementation.…”
Section: Findings Related To the Contributory Dimensions In Clinical supporting
confidence: 82%
See 1 more Smart Citation
“…In NHS study, 67% of responsible officers reported that they are ready to implement CG with consideration to "proactive risk management" dimension. This finding is in consistent with some of other studies (6,9,25,26). In these studies, preceding dimension has been considered as the most effective factor for quality improvement and facilitation of CG implementation.…”
Section: Findings Related To the Contributory Dimensions In Clinical supporting
confidence: 82%
“…There seen no significant differences between hospitals in this dimension (P> 0.05). Other studies have also found that the existence of a proactive and learning culture within hospitals has the highest correlation with successful CG implementation (25,33,34). Overall, studied hospitals were evaluated "weak to average" for CG implementation.…”
Section: Cg= Clinical Governancementioning
confidence: 97%
“…While each new definition has its own merit, none captured the essence of governance in terms of its impact on the total organisation. [4][5][6][7] It is impossible to circumscribe governance into a particular context. Its fundamental principles apply to all activities involved with the delivery of health care, whether financial, managerial or clinical.…”
Section: Introductionmentioning
confidence: 99%
“…Starey (2003) and Scally and Donaldson (1998) propose several components to facilitate the operationalization of clinical governance: clinical audit, clinical effectiveness, research and development, openness, risk management, education and training. Implementing clinical governance involves taking into consideration a whole set of organizational dimensions (Vanu Som, 2004;Brault et al, 2008) that will be helpful in making long-term changes to health care organizations. As such, the aims of clinical governance are to align managerial and clinical processes more closely to improve the quality and safety of care (Buetow and Roland, 1999) and to generate a new synergy between managers and clinicians to create new quality improvement initiatives (Pomey et al, 2008).…”
mentioning
confidence: 99%